Efektivitas Strategi Deradikalisasi Pada Narapidana Terorisme Di Rutan Cikeas - Dini Probowati (INC- Islam Nusantara Center, 2023)
The issue of radicalism and terrorism continues to get the attention of many parties around the world, including Indonesia causes damage to human life. For this reason, deradicalization efforts are urgent. However, the role of terrorism prisoners (Napiter) and former Napiter behind terrorism events that occurred in Indonesia raises questions about the effectiveness of deradicalization programs. This study aims to analyze the effectiveness of the deradicalization strategy in Napiter at Cikeas Detention Center implemented by Idensos Densus 88 AT and DeBintal Foundation, who are currently carrying out deradicalization program development activities at Super Maximum Security Detention Center specifically intended for terrorism suspects and become the initial place for the implementation of deradicalization programs against perpetrators of terrorism acts. This research was conducted using descriptive qualitative methods which are based on deradicalization and disengagement theories as well as the concept of deradicalization effectiveness indicators from Rabasa et al (2010). From this research, it is known that the deradicalization strategy carried out by Idensos Densus 88 AT and the DeBintal Foundation has a relatively acceptable level of acceptance by prisoners perpetrating terrorism acts in Cikeas Detention Center. This is because every prisoner in Cikeas detention center is